Community-based disaster communication management - Rochim, Mochamad; Bajari, Atwar; Damayanti, Ninis Agustini; Bakti, Iriana (Penerbit Universiti Kebangsaan Malaysia, 2020)
Indonesia is a country that is prone to disasters. To this relation, the government has created the National Disaster Management Agency (BNPB) and the Regional Disaster Management Agency (BPBD) in almost all provinces. However, the magnitude of the potential for disaster causes the government to feel the need for community support in disaster mitigation efforts. Community participation is absolutely necessary. It is in this context that the emergence of the community, in this case, the Garda Caah, is important. With the motto "Hope for the best, prepare for the worst," this community tries to help residents in flood prevention efforts and minimize the impact of flooding by providing immediate and continuous information. The aspect of managing communication and information is the most important part of this community. This study uses a qualitative method with a case study approach. The data collection techniques were carried out by interview, focus group discussion, and observation. There are two main results of this study namely (1) self-management of flood disaster anticipation based on the learning process, empowerment and volunteer activities, (2) the transition of traditional information systems that are modest to a new information system that is based on technology.